2016
DOI: 10.2174/1874325001610010836
|View full text |Cite
|
Sign up to set email alerts
|

An update on the Application of Nanotechnology in Bone Tissue Engineering

Abstract: Background: Natural bone is a complex and hierarchical structure. Bone possesses an extracellular matrix that has a precise nano-sized environment to encourage osteoblasts to lay down bone by directing them through physical and chemical cues. For bone tissue regeneration, it is crucial for the scaffolds to mimic the native bone structure. Nanomaterials, with features on the nanoscale have shown the ability to provide the appropriate matrix environment to guide cell adhesion, migration and differentiation.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 64 publications
(120 reference statements)
0
31
0
Order By: Relevance
“…2,3 The latest advances in the development of scaffolds using nanotechnology have given the surgeon new options for restoring the form and function of tissues and organs. 4,5 One of the most pivotal elements in bone tissue regeneration consists in creating and developing scaffolds, such as a biodegradable highly porous microstructure with interrelated pores and a large surface area, capable of mimicking the ECM microstructure, thus providing mechanical properties to support bone ingrowth. [4][5][6][7] In this context, electrospinning, a versatile and advanced technique for the production and fabrication of complex nanofibrous assemblies, attracted remarkable attention, essentially due to two different factors: (i) the capacity of structural mimicking of the natural tissues of ECM, and (ii) the possibility to process a wide range of materials together with a simple set-up and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3 The latest advances in the development of scaffolds using nanotechnology have given the surgeon new options for restoring the form and function of tissues and organs. 4,5 One of the most pivotal elements in bone tissue regeneration consists in creating and developing scaffolds, such as a biodegradable highly porous microstructure with interrelated pores and a large surface area, capable of mimicking the ECM microstructure, thus providing mechanical properties to support bone ingrowth. [4][5][6][7] In this context, electrospinning, a versatile and advanced technique for the production and fabrication of complex nanofibrous assemblies, attracted remarkable attention, essentially due to two different factors: (i) the capacity of structural mimicking of the natural tissues of ECM, and (ii) the possibility to process a wide range of materials together with a simple set-up and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 One of the most pivotal elements in bone tissue regeneration consists in creating and developing scaffolds, such as a biodegradable highly porous microstructure with interrelated pores and a large surface area, capable of mimicking the ECM microstructure, thus providing mechanical properties to support bone ingrowth. [4][5][6][7] In this context, electrospinning, a versatile and advanced technique for the production and fabrication of complex nanofibrous assemblies, attracted remarkable attention, essentially due to two different factors: (i) the capacity of structural mimicking of the natural tissues of ECM, and (ii) the possibility to process a wide range of materials together with a simple set-up and cost-effectiveness. [4][5][6][7][8][9] In particular, nanosurface modification by the electrospinning technique is able to control the protein adsorption and the biochemical construction of the protein layer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal-based nanomaterials are used for their high mechanical strength and include metals such as gold, silver, and titanium [8,9]. In contrast to bulk metals, metallic nanoparticles, due to quantum effects, can promote osseointegration in addition to promoting many other factors, such as osteoconductivity, mineralization, proliferation, osteoblast and chondrocyte cell adhesion, increased mechanical strength, stimulation of collagen production, stimulation of alkaline phosphatase activity, and stimulation of calcium deposition [8][9][10]. For instance, Tran and Webster found that iron oxide nanoparticles with a hydroxyapatite coating could increase osteoblast functions [11].…”
Section: Metallic Nanomaterialsmentioning
confidence: 99%